PERANAN GURU IPS DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK - Dian Handayani ST; Pargito Pargito; Sudjarwo Sudjarwo (Faculty of Teacher Training and Education, University of Lampung, 2015)
This research aimed to examine the role of social studies teachers in the character formation of students as well as factors that affect the teacher's role in shaping the character of students. The method used was qualitative with phenomenological approach. The research showed the role of social studies teachers as educators was realized by directing talents and abilities of learners, being responsible and realizing authority. IPS teachers as teacher was realized by planning and implementing learning. IPS teachers as role model is embodied in exemplary performances, social, and environmental stewardship. IPS teacher as trainer was realized by building awareness of learners, do characters that are taught together with teachers and learners.Penelitian ini bertujuan mengkaji peran guru IPS dalam pembentukan karakter peserta didik serta faktor yang mempengaruhi peran guru dalam pembentukan karakter peserta didik. Metode yang digunakan adalah kualitatif dengan pendekatan fenomenologi. Hasil penelitian menyatakan peran guru IPS sebagai pendidik diwujudkan dengan mengarahkan bakat dan kemampuan peserta didik, bertanggung jawab dan mewujudkan kewibawaan. Guru IPS sebagai pengajar diwujudkan dengan merencanakan serta melaksanakan pembelajaran. Guru IPS sebagai teladan diwujudkan dalam keteladanan penampilan, pergaulan, dan kepedulian terhadap lingkungan. Guru IPS sebagai pelatih diwujudkan dengan membangun kesadaran peserta didik, melakukan karakter yang diajarkan bersama guru dan peserta didik.Kata kunci: guru ips, pembentukan karakter, peran guru